TINJAUAN KESELAMATAN DAN KESEHATAN KERJA DI PENYIMPANAN REKAM MEDIS RUMAH SAKIT MATA BANDUNG EYE CENTER - Vera Dwi Astuti; Dimas Yuda Permana (INFOKES (Informasi Kesehatan), 2020)
This study aimed to determine how Occupational Health And Safety Review On Medical Records Storage In Bandung Eye Center Hospital. The research method used is qualitative with a descriptive approach. Data collection techniques used were interviews, observation, and literature review. The sampling technique uses a non-probability sampling technique, in which the sample is taken improperly during the research. The research location is in the medical record installation of Bandung Eye Center Eye Hospital. From the results of research conducted regarding occupational safety and health in medical record storage, there are problems, including: (1). There is no specific SOP that regulates occupational safety and health in the medical record storage room of the Bandung Eye Center Eye Hospital (2). The medical record officers are not aware of the use of gloves, (3). The air conditioner is not working properly and often does not turn on which causes the room temperature to get hot. The author's suggestions for solving the problem are: (1). Creating a special SOP that regulates occupational safety and health in the storage room of the Bandung Eye Center Eye Hospital medical records, (2). It is recommended that the use of personal protective equipment in the storage room be increased, especially the use of gloves (3). Check and repair work tools, especially air conditioners, which are often broken regularly. (4). Provide training and socialization of occupational safety and health to officers so that officers are more skilled and understand the risks that arise in the work environment.